Role of Physics Community for the Development and Advancement of Physics Education in the Globalization Era - Khalijah Mohd. Salleh (Institut Teknologi Bandung, 2004)
Knowledge of science generally and physics in particular is no longer the prerogative of the practicing scientists or physicists but has to be disseminated to the public. Thus physics education can be expected to play an important role in the era of globalisation. Physics education provides a person with the knowledge and understanding about how the physical world works. The knowledge and skills required by individuals differ, as different individuals need different levels of physics knowledge and skills. The decline in physics enrolment in schools and subsequently in institutions of higher learning has caused a serious shortage of candidates for physics teaching. Subsequently schools have only 4.7 percent teachers with background in physics. The balanced is made up by non-physics option teachers. These non-option physics teachers want to strengthen their physics background knowledge and understanding, and experimental skills. Science teachers and curriculum planners especially at school level are left on their own to conceptualise science and translate to the best of their ability the science curriculum content into classroom activities. Their understanding of what science is depends on what they have learnt from their professors or teachers.The presence of the physics community in the education sector is urgently needed. Physicists are the ones who better understanding of the nature of physics, how to think physics and how to approach physics experiments and problem solving. These aspects of physics make up the culture of physics. Physics societies need to include in their conferences or seminars topics related to the education and training of future physicists, their career development, and ultimately public awareness of physics to ensure a continuous supply of physicists for future needs. What need to be noted is that when teachers interact with physicists, they will sooner or later identify themselves with physics and the physics community. Only then teaching physics becomes more meaningful and satisfying. Teachers can be expected to be more committed to and responsible in teaching physics to their pupils. Physics education has a role in human resource development that a country needs to achieve the nations’ developmental goals. There are different levels of physics that are needed by different groups of people. The fact that the system of education could not really overcome the perceptions that physics is difficult dry and dull requires input by the physics community to help inject the kind of excitement that physicists have when they do physics. There are many roles that the physics community can play towards curriculum development, innovating new approaches to physics teaching and learning. Physics societies are invited to give space for physics education in their technical meetings so as to bridge the gap that currently divide the physics community from the physics educators and the public at large.